Visibility and impact of the scientific production on cranial nerve teaching and learning published in Scopus - Garces Ginarte, Mario Javier; Landrove-Escalona, Eduardo Adiel; Moreno-Cubela, Fidel Jesús; Toledo del Yano, Roxana (Data & metadata, 2022)
Introduction: the study of the nervous system constitutes a generally tricky element for students of the basic cycle of medical sciences, being content of particular interest the teaching-learning process of the cranial nerves.Objective: to describe the visibility and impact of scientific production in Scopus on teaching-learning of the cranial nerves.Method: a bibliometric analysis of the articles on teaching-learning of the cranial nerves was carried out in the Scopus database between 2017 and 2021. Production, visibility, and impact variables were studied, such as the number of documents and citations and the impact of weighted citations.Results: 64 articles were published, with a production peak in 2019 (25 %; n=16). The articles received 282 citations, of which 30,6 % correspond to 2017. The highest weighted citation impact value was reported in 2017 (1,3). 13,3 % of the articles were written in international collaboration, and 7,2 % had sole authorship. The national collaborative works presented a higher average number of citations per publication (4,9; n=163) and a better impact index of weighted citations (1,14).Conclusions: a low scientific production on teaching-learning of the cranial nerves was found, with a tendency to decrease, with a predominansce of multiple authorship, mainly national and institutional. A low-impact index of the publications was found according to their citations